Alf Ross : a life - Evald, Jens (DJØF Publishing, 2014)
This is the story of Alf Ross, one of the founding fathers of the so-called Scandinavian legal realism. On the surface, the life of Alf Ross was a fairy tale; at least he had to go through an awful lot of hardship both in relation to love and work before he became an internationally known and recognized philosopher and legal scholar. But the story of Alf Ross is not a fairy tale. It is the story about a man's struggle to greatness and the consequences of such a struggle in his relationship with other people including his spouse. This is the story that is told in the book on Alf Ross. Published wi.